S(vi) Lewis acids: fluorosulfoxonium cations. Issue 84 (13th September 2016) - Tsao, Fu An; Waked, Alexander E.; Cao, Levy; Hofmann, Jordan; Liu, Lei; Grimme, Stefan; Stephan, Douglas W.
Abstract : Avenues to S-based Lewis acids were developed via the oxidation of aryl-sulfoxides with XeF2, giving difluorodiarylsulfoxides which react via fluoride abstraction to afford Lewis acidic fluorosulfoxonium cations; this acidity is derived from the S–F σ* orbital and has been probed both experimentally and computationally. Abstract : Avenues to S-based Lewis acids were developed via the oxidation of aryl-sulfoxides with XeF2, giving difluorodiarylsulfoxides which react via fluoride abstraction to afford Lewis acidic fluorosulfoxonium cations; this acidity is derived from the S–F σ* orbital and has been probed both experimentally and computationally.